Determining Volt/Var Characteristics of Electric Vehicle Charging Station Inverters for Voltage Regulation in Distribution Networks - Vyacheslav Voronin; Fedor Nepsha; Pavel Ilyushin (World Electric Vehicle Journal)
In this paper, a method for determining the parameters of the Volt/Var characteristics of inverters of electric vehicle charging stations to regulate voltage in distribution networks is proposed, which differs from the existing ones by taking into account the possibility of the joint control of active and reactive power and the impedance of the power distribution line. The method proposed in this paper allows researchers to determine the slope and width of the dead band of the Volt/Var characteristics according to the criterion of limiting the maximum voltage deviations to an acceptable value or maximizing the reactive power of the inverter upon reaching a specified voltage. To test this method, a quasi-dynamic modeling of the distribution network with electric vehicle charging stations regulating voltage using the Volt/Var characteristics was performed. Based on the modeling results, it is shown that fast electric vehicle charging stations can be used to regulate voltage in the distribution network with relatively minor constraints on the charging active power.